Contemporary strategies in the diagnosis and treatment of juvenile jdiopathic arthritis: imaging techniques and therapeutic advances - Czyż, Sandra; Saracen, Nina; Marszał, Wiktoria; Nowak, Karolina; Mistarz, Wiktoria; Sysło, Oliwia (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease in children, involving not only joints but also internal organs, skin, and eyes. It is diagnosed in children under the age of 16 when symptoms last longer than six weeks. The ILAR classification includes several subtypes such as oligoarticular, polyarticular (RF-positive and RF-negative), systemic (sJIA), psoriatic, and enthesitis-related arthritis. Systemic JIA is characterized by fever and rash, while the oligoarticular form often coexists with positive ANA antibodies and carries a high risk of chronic uveitis. New subtypes have been added in recent years, such as early-onset ANA-positive JIA. Imaging, including X-ray, MRI, and ultrasound, plays a crucial role in assessing disease progression, especially in the hip, knee, and temporomandibular joints. Treatment involves a multidisciplinary approach and includes NSAIDs, intra-articular and systemic glucocorticoids, non-biologic DMARDs (especially methotrexate), and biological therapies. Biologic agents include TNF inhibitors (adalimumab, etanercept, infliximab), IL-1 inhibitors (anakinra, canakinumab), IL-6 inhibitor (tocilizumab), T-cell inhibitor (abatacept), and B-cell therapy (rituximab). These targeted treatments improve disease control, reduce joint damage, and enhance quality of life, enabling many patients to achieve remission and prevent long-term disability.